The Role of Women Entrepreneurs in the Weaving Industry in Bima City in Improving Household Welfare - Adinda Riska Saputri; Fajrin Hardinandar; Nursani Nursani (JURNAL ECONOMINA, 2026)
This study aims to analyze the influence of social capital on the household welfare of women entrepreneurs in the weaving industry in Bima City. Social capital is measured through three dimensions: bonding social capital, bridging social capital, and linking social capital, with demographic factors as control variables, including education level, number of household members, and length of business. The study used a quantitative approach with explanatory sequential mixed methods. Quantitative data were obtained through questionnaires distributed to women entrepreneurs in the weaving industry in Bima City, while qualitative data were obtained through interviews and observations to support the analysis. Data analysis was conducted using binary probit regression to test the influence of social capital on the probability of households achieving welfare status. The results showed that linking social capital has a positive influence on the opportunity to achieve household welfare, while bonding social capital and bridging social capital have not shown a significant influence. In addition, education level also contributes to improving household welfare. These findings indicate that access to formal institutions, government, financial institutions, and empowerment programs play an important role in improving the household welfare of women entrepreneurs in the weaving industry in Bima City.